Replacing maize with low tannin sorghum grains: lamb growth performance, microbial protein synthesis and enteric methane production - Soltan, Yosra; Abdalla Filho, Adibe; Abdalla, Adibe; Berenchtein, Bernardo; Schiavinatto, Patricia; Costa, Ciniro [UNESP] (Csiro Publishing, 2021)
Context. Sorghum (Sorghum bicolor (L.) Moench) grain with low tannin content may be suitable as an alternative to maize (Zea mays L.) grain in ruminant diets in terms of input costs and drought tolerance, and effects on growth performance and mitigation of methane (CH4) emissions. Aims. The study aimed to evaluate the effects of substitution of maize with sorghum grain at different rates on ruminal microbial protein synthesis, CH4 formation and liveweight gain in growing ruminants. Methods. Twenty-five Santa Ines lambs (bodyweight 19.0 +/- 1.5 kg) were randomly divided into five dietary treatments. Control diet components (on a dry matter basis) were Tifton-85 hay (400 g/kg), maize (405 g/kg), soybean meal (165 g/kg) and commercial mineral supplement (30 g/kg). Sorghum diets comprised the basal diet with the maize grain proportionately substituted with sorghum grain at 25%, 50%, 75% and 100% (diets S-25-S-100). Lamb feed intake, growth performance, nutrient digestibility, nitrogen balance, microbial protein synthesis and CH4 emission were measured during an experimental period of 70 days. Key results. Negligible variations of chemical composition were observed among the experimental diets, although numerical increases in condensed tannins were observed with increasing levels of sorghum replacement. There was no significant effect of level of sorghum inclusion on feed intake. Partial substitution of maize with sorghum grain increased lamb average daily gain linearly (P = 0.02) and quadratically (P = 0.002) compared with diets based on either grain alone, with the S-50 lambs having the highest values. A linear decrease in dry matter digestibility (P = 0.02), organic matter (P = 0.02) and acid detergent fibre (P = 0.002) was observed for lambs receiving sorghum diets compared with the control. A significant linear (P = 0.023) effect was observed for retained nitrogen (g/day), with lambs fed S-25 and S-50 having higher values than those in other treatments. All partially substituted diets (S-25, S-50 and S-75) reduced CH4 per unit bodyweight gain in a linear trend (P = 0.03), by 35%, 29% and 33%, respectively, and tended to increase (linear effect, P = 0.09) the calculated amounts of absorbed microbial protein compared with the control diet. Conclusions. Low tannin sorghum grains can replace maize grains by up to 75% to maximise ruminal microbial biomass production for optimal lamb growth performance and reduced CH4 emission.
Keywords: methane; carbohydrates; condensed tannins; digestibility; purine derivatives